A new seabed mobility index for the Irish Sea: Modelling seabed shear stress and classifying sediment mobilisation to help predict erosion, deposition, and sediment distribution. (1st November 2021) - Coughlan, Mark; Guerrini, Marco; Creane, Shauna; O'Shea, Michael; Ward, Sophie L.; Van Landeghem, Katrien J.J.; Murphy, Jimmy; Doherty, Paul
Abstract: The seafloor is increasingly being used for siting renewable energy and telecommunication infrastructure as well as supporting key fisheries and biodiversity. Understanding seabed stability and sediment dynamics is, therefore, a fundamental need for offshore engineering and geoscience and biological studies. In this study we aim to quantify the levels of sediment mobility in the Irish Sea: an area of increasing socio-economic interest and subsequent seabed pressures. The temporal and spatial interaction between bathymetry, hydrodynamics and seabed sediments leads to a complex pattern of erosion, bedload transport and deposition which can affect seabed infrastructure and modify habitats. Information on current and wave conditions were obtained from numerical modelling to assess their role in generating seabed hydrodynamic conditions. These outputs were coupled with observed seabed grain-size data to predict the exceedance of sediment mobility thresholds by bed shear stress values for a period of one year according to empirical formulae. Exceedance frequency values were used to calculate a number of sediment disturbance and mobility indexes to allow for a robust assessment of sediment dynamics. Sediment in the Irish sea, on average, is being mobilised 35% of the time during the year, with 35% of the spatial area studied being mobilised over 50% of the time. Even in areas of low sediment mobilisation frequency (<5%), there are implications for bedform dynamics. The spatial patterns of the calculated sediment mobility are discussed in the context of current seabed geomorphology and the implications for both engineering and environmental considerations. Highlights: A 2D hydrodynamic model and a spectral wave model were developed to assess sediment mobilisation in the Irish Sea. Sediment mobility indices calculated for combined wave-current sediment mobilisation. 35% of the sediment coverage spatially within the study area is mobilised 50% of the year, some areas higher than 90%. Only 2% of the study area was calculated as experiencing 0% sediment mobility. Sediment mobility maps can be used in siting offshore infrastructure and to inform effective marine management.